Dual‐Specificity Phosphatase 26 Protects Against Cardiac Hypertrophy Through TAK1 - Zhao, Jing (J Am Heart Assoc, 2021)
BACKGROUND: Heart pathological hypertrophy has been recognized as a predisposing risk factor for heart failure and arrhythmia. DUSP (dual‐specificity phosphatase) 26 is a member of the DUSP family of proteins, which has a significant effect on nonalcoholic fatty liver disease, neuroblastoma, glioma, and so on. However, the involvement of DUSP26 in cardiac hypertrophy remains unclear. METHODS AND RESULTS: Our study showed that DUSP26 expression was significantly increased in mouse hearts in response to pressure overload as well as in angiotensin II–treated cardiomyocytes. Cardiac‐specific overexpression of DUSP26 mice showed attenuated cardiac hypertrophy and fibrosis, while deficiency of DUSP26 in mouse hearts resulted in increased cardiac hypertrophy and deteriorated cardiac function. Similar effects were also observed in cellular hypertrophy induced by angiotensin II. Importantly, we showed that DUSP26 bound to transforming growth factor‐β activated kinase 1 and inhibited transforming growth factor‐β activated kinase 1 phosphorylation, which led to suppression of the mitogen‐activated protein kinase signaling pathway. In addition, transforming growth factor‐β activated kinase 1–specific inhibitor inhibited cardiomyocyte hypertrophy induced by angiotensin II and attenuated the exaggerated hypertrophic response in DUSP26 conditional knockout mice. CONCLUSIONS: Taken together, DUSP26 was induced in cardiac hypertrophy and protected against pressure overload induced cardiac hypertrophy by modulating transforming growth factor‐β activated kinase 1–p38/ c‐Jun N‐terminal kinase–signaling axis. Therefore, DUSP26 may provide a therapeutic target for treatment of cardiac hypertrophy and heart failure.